2008
DOI: 10.1111/j.1365-2109.2008.02021.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of stocking density on the growth performance and yield of Nile tilapia [Oreochromis niloticus(L., 1758)] in a cage culture system in Lake Kuriftu, Ethiopia

Abstract: This research was conducted to investigate the e¡ect of stocking density on the growth performance and yield of Oreochromis niloticus in cage culture in Lake Kuriftu. The treatments had stocking densities of 50 (50F), 100 (100F), 150 (150F), and 200 (200F) ¢sh per m À 3 . All treatments were in duplicate. Juveniles with an average weight of 45. 76 AE 0.25 g were stocked in the treatments. The ¢sh were fed a composite mixture of mill sweeping, cotton seed, and Bora food complex at 2% of their body weight twice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
22
6
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 35 publications
(40 reference statements)
14
22
6
2
Order By: Relevance
“…Stocking density can affect the survival rate in fish culture (Hargreaves et al, 1991;Wallat et al, 2004;Watanabe et al, 1990), influencing growth, survival, and behavioral interactions (Brown et al, 1992;Christiansen et al, 1992;Cruz and Ridha, 1991;Irwin et al, 1999). Similar results have been confirmed in freshwater fish (Gibtan et al, 2008;Yi et al, 1996;Zhu et al, 2011), and it is well-accepted that high-density stocking can cause reductions in growth rate and increases in mortality (Kincaid et al, 1976;Lee et al, 1996;McClain, 1995;Mills and McCloud, 1983;Morrissy, 1992). However, conflicting results have linked lowdensity culture with high mortality in rainbow trout (Oncorhynchus mykiss) and salmon (Refstie, 1977), and high-density culture with an increased growth rate, survival rate, and efficiency of food conversion in juvenile silver perch (Bidyanus bidyanus) and tilapia (Oreochromis spirulus) (Cruz and Ridha, 1991;Rowland et al, 2006;Watanabe et al, 1990).…”
Section: Discussionsupporting
confidence: 79%
“…Stocking density can affect the survival rate in fish culture (Hargreaves et al, 1991;Wallat et al, 2004;Watanabe et al, 1990), influencing growth, survival, and behavioral interactions (Brown et al, 1992;Christiansen et al, 1992;Cruz and Ridha, 1991;Irwin et al, 1999). Similar results have been confirmed in freshwater fish (Gibtan et al, 2008;Yi et al, 1996;Zhu et al, 2011), and it is well-accepted that high-density stocking can cause reductions in growth rate and increases in mortality (Kincaid et al, 1976;Lee et al, 1996;McClain, 1995;Mills and McCloud, 1983;Morrissy, 1992). However, conflicting results have linked lowdensity culture with high mortality in rainbow trout (Oncorhynchus mykiss) and salmon (Refstie, 1977), and high-density culture with an increased growth rate, survival rate, and efficiency of food conversion in juvenile silver perch (Bidyanus bidyanus) and tilapia (Oreochromis spirulus) (Cruz and Ridha, 1991;Rowland et al, 2006;Watanabe et al, 1990).…”
Section: Discussionsupporting
confidence: 79%
“…Whilst aspects of these outputs concur with Taylor et al (2004), who concluded B. barbus growth in lentic fisheries was suppressed when the stock density of C. carpio exceeded 1000 kg ha −1 , they also demonstrate that growth will be similarly suppressed if the stocked species are T. tinca and B. barbus. This relationship between increasing stock abundance and reduced somatic growth is consistent with studies on other species completed primarily for aquaculture purposes, covering species such as brown trout Salmo trutta (Linnaeus, 1758) (Bohlin et al, 2002) and Nile tilapia Oreochromis niloticus (Linnaeus, 1758) (Gibtan et al, 2008).…”
Section: Discussionsupporting
confidence: 72%
“…Similarly, stocking density of fingerlings of silver perch, Bidyanus bidyanus, stocked at 100 or 200 fish/m3 was not influenced survival. Several studies have also shown that the density have not significantly effect on survival of rainbow trout, Oncorhynchus mykiss [18], tambaqui, Colossoma macropomum [19] and Oreochromis niloticus [20]. Conversely with these study, it found in the endangered teleost species piabanha, Brycon insignis was higher survival at low stocking density [13].…”
Section: Water Quality Parameterscontrasting
confidence: 54%